The life of Anne Frank - Saunders, Nicholas J. (Columbus, OH : School Specialty Pub., 2006)
Presents stories from the life of Anne Frank in graphic novel form, beginning with the rise of the Nazis in pre-World War II Germany, and continuing to her death in a concentration camp.
Includes index.
3.7
3-6
Keywords: Frank, Anne, -- 1929-1945 -- Comic books, strips, etc. -- Juvenile literature; Jewish children in the Holocaust -- Netherlands -- Amsterdam -- Biography -- Comic books, strips, etc. -- Juvenile literature; Jews -- Netherlands -- Amsterdam -- Biography -- Comic books, strips, etc. -- Juvenile literature; Holocaust, Jewish (1939-1945) -- Netherlands -- Amsterdam -- Comic books, strips, etc. -- Juvenile literature; Frank, Anne, -- 1929-1945 -- Cartoons and comics; Jewish children in the Holocaust -- Netherlands -- Amsterdam -- Biography -- Cartoons and comics; Jews -- Netherlands -- Amsterdam -- Biography -- Cartoons and comics; Holocaust, Jewish (1939-1945) -- Netherlands -- Amsterdam -- Biography -- Cartoons and comics; Amsterdam (Netherlands) -- Biography -- Cartoons and comics; Cartoons and comics; Frank, Anne, -- 1929-1945 -- Comic books, strips, etc; Jews -- Amsterdam (Netherlands) -- Biography -- Comic books, strips, etc; Holocaust, 1933-1945 -- Biography -- Comic books, strips, etc; Amsterdam (Netherlands) -- Biography -- Comic books, strips, etc; Comic books, strips, etc